PERAN KANTOR URUSAN AGAMA (KUA) DALAM UPAYA MENANGGULANGI PERNIKAHAN SIRRI DI KOTA BANDAR LAMPUNG - Bunyamin, Bunyamin (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2020)
The phenomenon of sirri marriages has long been happening in Indonesia. Sirri marriages also caused controversy from various parties on the grounds that they were detrimental to women. Sirri marriages are actions carried out in hiding, some are recorded but hidden from the community and some are not registered with the Marriage Registration Officer (PPN) and are not registered at the Office of Religious Affairs (KUA). This study aims to determine and understand how the role of the Office of Religious Affairs (KUA) in an effort to overcome sirri marriages in Bandar Lampung City. This research uses field research methods with institutional approaches, law science and Islamic law. The conclusion of this study is that the role played by the Office of Religious Affairs (KUA) in overcoming sirri marriages is by conducting socialization. The efforts made by the KUA are to provide counseling, education, appeals and guidance to the community in general and for the prospective bride and groom in particular